DETERMINANTS OF QUALITATIVE RISK ASSESSMENT OF CRIMINAL OFFENSES IN THE NATIONAL ECONOMY SECTOR - CHYNCHYK, Anatolii; HOLUBKA, Stepan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents the authors’ understanding of qualitative risk assessment of criminal offenses in the national economy sector, based on the premise that the mission of qualitative risk analysis is to identify the sources and causes of risk at each stage of its formation.The content and key scientific principles of assessing qualitative indicators are revealed. These principles involve the use of expert methods necessary for preparing, selecting, and evaluating risks, as well as making substantiated, rational, and effective decisions in risk management within the economic domain.The article substantiates a qualitative indicator that enables evaluation (together with quantitative indicators of criminal offenses) of deviations in the priorities of a state body responsible for implementing national policy in a particular sector (budgetary, tax, customs, monetary-credit, or investment) from the actual execution of that policy based on a defined risk or its components.It is determined that the qualitative indicator reflects the opinion of the expert community within the institution, in accordance with its powers and based on relevant knowledge and experience.Based on the analysis of existing expert assessment methods, the study updates and proposes a questionnaire for assessing the risk of committing a criminal offense. Taking into account the specifics of this research, the questionnaire is divided into institutional blocks according to the competence of state bodies within the risk cluster.The paper emphasizes the crucial role of principles that perform integrative, synthesizing, and organizing functions in risk assessment. These principles are visualized as the coverage of powers of the relevant state institution concerning the management of the risk of criminal offenses or the phenomena that form them.As a result of the study on qualitative risk indicators, the necessity for the development and testing of methodological approaches to assessing quantitative indicators is substantiated.
Keywords: national economy; state bodies; Bureau of Economic Security of Ukraine; economic security; qualitative risk analysis; quantitative risk analysis; assessment; qualitative indicators; risks; criminal offense risk; determinants; institution